(3GdJLGQI GdGdcJQhfjI (B:s (3GdeSJbHd GdhGYO ddGLjGd GdbGOeI (B/s - (3GdWGFj, eMeO YHO MSjfs ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2010)
(3GdJLGQI GdGdcJQhfjI (B: (3eGgjJgG , feGPLgG , NUGFUgG , CgejJgG , eMOOGJgG , GdHfjI GdJMJjI ddJLGQI GdGdcJQhfjI h HfGA ehbY GdhjH , JWHjbGJ GdJLGQI GdGdcJQhfjI (B: (3GdHfhc GdGdcJQhfjI , GdMLR GdGdcJQhfj , GdHMK Yf GdhXGFa GdcJQhfjG , GdJYdje GdGdcJQhfj , GdGYdGfGJ GdGdcJQhfjI , GdfTQ GdGdcJQhfj , GdeRGOGJ GdGdcJQhfj , GdMcheI GdGdcJQhfjI , GdSjGMI GdGdcJQhfjI , GdJShb GdGdcJQhfj , SdSdI GdJRhjO GdGdcJQhfjI (B.s
(3eQGLY U(B.505 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdJLGQIs; (3GdJLGQI GdOhdjIs; (3GdJLGQI(B- (3GdEdcJQhfjIs